Portuguese nurses’ stress, anxiety, and depression reduction strategies during the COVID-19 outbreak - Pinho, Lara Guedes de (2021)
The COVID-19 pandemic has contributed to mental health problems worldwide. Nurses are particularly prone to stress because they directly care for individuals with suspected or confirmed cases of COVID-19. The aims of this study were (a) to explore the association between the mental health promotion strategies used by nurses during the COVID-19 outbreak and their symptoms of depression, anxiety, and stress; (b) to compare the symptoms of depression, anxiety, and stress of mental health nurses to those of non-mental health nurses; and (c) to compare the frequency of use of mental health strategies of mental health nurses to those of non-mental health nurses. A cross-sectional study was conducted with a sample of 821 nurses. Univariate and multivariate regression models were developed to identify potential protective factors of depression, anxiety, and stress. The chi-square test was also used to compare the use of strategies among mental health and non-mental health nurses. Portuguese nurses demonstrated high symptoms of depressive symptoms, stress, and anxiety. Healthy eating, physical activity, rest between shifts, maintaining social contacts, verbalizing feelings/emotions, and spending less time searching for information about COVID-19 were associated with better mental health. Mental health nurses had less depression, anxiety, and stress, and used more strategies to promote mental health than other nurses. We consider it important to promote nurses’ mental health literacy by encouraging them to develop skills and strategies aimed at improving their resilience and ability to deal with difficult situations while caring for the population.